1983
DOI: 10.1524/ract.1983.33.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Decay-Induced Bromination via the 76Kr(EC)76Br and 77Kr (β+, EC)77Br Decay

Abstract: Substitution reactions by nucleogenic bromine ions generated in situ via the 76 ' 77 Kr(/3 + , EC) 76,77 Br decay processes were examined in gaseous fluorobenzene and para-difluorobenzene. In the Krmoderated systems at atmospheric pressure only small yields (0.2 to 2 %) of hydrogen and fluorine substitution can be observed. A small nuclear isotope effect (1.2 to 2) with preference for 77 Br substitution products is found independent of the mole fraction of krypton moderator gas present. Fluorine substitution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…Furthermore, intermolecular competition experiments performed with 38 CI, 12S I and 211 At in equimolar mixtures of chlorobenzene with substituted chlorobenzenes [42] have shown a limited but definite dependence of the replacement ratios on the Hammett substituent constant. A similar dependence has been found by other groups for 38 CI [31], 76 Br and 77 Br [36,37] replacing hydrogen in monosubstituted benzenes. As can be seen from On the other hand, no dependence on the substituent constants could be detected for I8 F replacing chlorine nor for 38 CI replacing fluorine in analogous intermolecular competition experiments, which may indicate a different reaction mechanism in these cases [42].…”
Section: Halogen Replacementsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, intermolecular competition experiments performed with 38 CI, 12S I and 211 At in equimolar mixtures of chlorobenzene with substituted chlorobenzenes [42] have shown a limited but definite dependence of the replacement ratios on the Hammett substituent constant. A similar dependence has been found by other groups for 38 CI [31], 76 Br and 77 Br [36,37] replacing hydrogen in monosubstituted benzenes. As can be seen from On the other hand, no dependence on the substituent constants could be detected for I8 F replacing chlorine nor for 38 CI replacing fluorine in analogous intermolecular competition experiments, which may indicate a different reaction mechanism in these cases [42].…”
Section: Halogen Replacementsupporting
confidence: 89%
“…Somewhat unexpectedly this has been found to be true not only for halogens forming in (n, 2n) and (η, γ) nuclear processes with high initial kinetic energy [25,26] but also for those originating via EC with relatively low kinetic and high ionization and excitation energy [27,36,37], This indicates fast neutralization of originally ionized recoil species [36,37,39] followed by their reactions as neutral atoms that still possess definite excess energy.…”
Section: Halogen Replacementmentioning
confidence: 88%
See 1 more Smart Citation
“…[10] have observed the selectivity among the three chlorotoluenes in 1:1:1 mixtures of these Compounds. COENEN et al [16], however, reported a relatively unselective pattem in the reactions of "Br with toluene. They attributed this to the relatively low activation and competing side product formation.…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular competition experiments were carried out with equimolar liquid mixtures of mono-and disubstituted benzene derivatives in order to reduce the possible influence of different media on the slowing down process of recoil atoms, which could alter the replacement ratios if obtained in systems having different moderator properties as was described earlier by Coenen et al [9,10] and Moerlein et al [11],…”
Section: Introductionmentioning
confidence: 99%